2013
DOI: 10.1088/0004-637x/781/1/15
|View full text |Cite
|
Sign up to set email alerts
|

Vacuum Ultraviolet Emission Spectrum Measurement of a Microwave-Discharge Hydrogen-Flow Lamp in Several Configurations: Application to Photodesorption of Co Ice

Abstract: We report measurements of the vacuum ultraviolet (VUV) emission spectra of a microwave-discharge hydrogenflow lamp (MDHL), a common tool in astrochemistry laboratories working on ice VUV photoprocessing. The MDHL provides hydrogen Ly-α (121.6 nm) and H 2 molecular emission in the 110-180 nm range. We show that the spectral characteristics of the VUV light emitted in this range, in particular the relative proportion of Ly-α to molecular emission bands, strongly depend on the pressure of H 2 inside the lamp, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
112
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 104 publications
(130 citation statements)
references
References 45 publications
17
112
1
Order By: Relevance
“…The systematic approach presented here allows the optimization of lamp settings for specific experiments, using the MDHL in a more wavelength selective way. The study complements the work of Chen et al (2014) and more recently Es-sebbar et al (2015). The main difference between the present work and these two recent studies is that the spectral irradiance of the MDHLs is characterized absolutely, using a fully calibrated measurement procedure.…”
Section: Introductionmentioning
confidence: 63%
See 1 more Smart Citation
“…The systematic approach presented here allows the optimization of lamp settings for specific experiments, using the MDHL in a more wavelength selective way. The study complements the work of Chen et al (2014) and more recently Es-sebbar et al (2015). The main difference between the present work and these two recent studies is that the spectral irradiance of the MDHLs is characterized absolutely, using a fully calibrated measurement procedure.…”
Section: Introductionmentioning
confidence: 63%
“…Photodesorption rates for several molecules using synchrotron radiation (Fayolle et al 2011(Fayolle et al , 2013 as well as direct cross section measurements of the main constituents of interstellar ice show strong wavelength dependences in the VUV domain. (Cruz-Diaz et al 2014a,b) Recently, Chen et al (2014) showed that the differences in CO photodesorption rates reported by various groups over the past decade may be partly explained by differences in MDHL emission spectra. Carbon monoxide is an excellent example, since it strongly absorbs 160 nm photons while Lyman-α photons are clearly off resonance, as has been shown in independent experiments (Fayolle et al 2011;Cruz-Diaz et al 2014a).…”
Section: Introductionmentioning
confidence: 99%
“…The experiments have been performed with the interstellar photoprocess system (IPS; Chen et al 2014). The soft X-ray source is the Spherical Grating Monochromator beamline at NSRRC covering the energy range from 0.25 to 1.2 keV.…”
Section: The Co Ice Irradiationmentioning
confidence: 99%
“…Thus, the spectral shape of the illuminating source became crucial in the interpretation of the experiments. Chen et al (2014) performed an accurate analysis of the vacuum ultraviolet emission spectra of a microwave-discharge hydrogen flow lamp commonly used in studies of ice processing, owingto its intense Lyα emission at 121.6 nm and molecular hydrogen (mainly) Lyman and Werner emission bands. These authors show that the spectral characteristics of the radiation depend on a number of technical details, such as the relative proportions of atomic and molecular hydrogen, and that such characteristics determine the yield of CO photodesorption.…”
Section: Comparison With Other Experimentsmentioning
confidence: 99%
See 1 more Smart Citation